2006
DOI: 10.1055/s-2006-933341
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Factor in Cancer and Angiogenesis: The Molecular Link between Genetic Tumor Progression, Tumor Neovascularization, and Cancer Coagulopathy

Abstract: Tissue factor (TF), the primary cellular initiator of blood coagulation, is also involved in cancer-related processes such as hypercoagulability (Trousseau syndrome), tumor growth, angiogenesis, and metastasis. Indeed, elevated TF expression by cancer cells and their associated endothelial cells has been reported frequently. Oncogenic events in cancer cells (e.g., expression of mutant K- ras, EGFR, PTEN or p53) lead to an increase in TF levels and activity, and thereby promote tumor aggressiveness, angiogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
130
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(136 citation statements)
references
References 134 publications
(304 reference statements)
0
130
0
3
Order By: Relevance
“…This drastic upregulation may, to some extent, be caused by the existence of common tumor microenvironmental stimuli, such as those responsible for TF upregulation during inflammation and hypoxia. Recently, it was shown that TF expression is under the direct control of oncogenic pathways activated by genetic mutations sustained by cancer cells (28). This is shown experimentally by the effect of several mutant oncogenes, including K-ras, EGFR, EGFRvIII, HER-2, and PML-RARa on TF transcription, translation, halflife, and encryption.…”
Section: Discussionmentioning
confidence: 99%
“…This drastic upregulation may, to some extent, be caused by the existence of common tumor microenvironmental stimuli, such as those responsible for TF upregulation during inflammation and hypoxia. Recently, it was shown that TF expression is under the direct control of oncogenic pathways activated by genetic mutations sustained by cancer cells (28). This is shown experimentally by the effect of several mutant oncogenes, including K-ras, EGFR, EGFRvIII, HER-2, and PML-RARa on TF transcription, translation, halflife, and encryption.…”
Section: Discussionmentioning
confidence: 99%
“…47 The presence of MP in the tumor microenvironment may be explained by the fact that several types of cancer express TF leading to platelet activation and release of MP, which in turn may affect several aspects of tumor cell biology. 56 We studied the influence of MP on the biology/metastasis of cancer cells in more detail in experimental models of lung and breast cancers. 47 We found that MP stimulated the phosphorylation of MAPKp42/44 and serine/threonine kinase in these cells as well as the expression of membrane type 1-matrix metalloproteinase (MT1-MMP).…”
Section: Mp -Platelet-derived MVmentioning
confidence: 99%
“…Factor VIIa (FVIIa) then binds to TF on the cell surface. Sequential downstream activation of haemostatic protease complexes leads to the generation of thrombin, with subsequent platelet activation and the formation of a fibrin clot, which restores vessel integrity (reviewed by Rak et al, 2006).…”
mentioning
confidence: 99%